The Impact of the European Neighborhood Policy on Jordan Economically, Politically and Security (2004-2021) - Dardour, Walaa Ali; Diabat, Kheir Salem (Dirasat: Human and Social Sciences, 2024)
Objectives: The study seeks to investigate the extent of Jordanian-European cooperation within the framework of the "European Neighborhood Policy" (ENP), which emanate from the Euro-Mediterranean Partnership (Barcelona) 1995, with the aim of developing a partnership with neighboring countries and establishing a prosperous, more secure, and stable region. Methods: The study analyzed the agreement and evaluated its outputs in the light of the interests achieved for the two parties, by focusing on the national interest approach, and the institutional (legal) approach to determine the behaviors and outputs of the (ENP). Results: Despite the European Union's financial support to Jordan for Neighborhood Policy objectives, the outcomes were not significantly positive. Jordan implemented various programs and reform plans, but the national debt increased to 92.4% of the GDP in 2019. Trade with the EU did not improve, resulting in a 2021 trade deficit of 2,900 million euros. Politically, limited partnership results were observed, with Jordan ranking 118th in the 2020 Democracy Index and 58th in the Corruption Perceptions Index. The Journalism and Independence Index placed Jordan at 129 out of 180 countries in 2021. Conclusions: The (ENP) developed some aspects of the Jordanian-European partnership and did not have an actual and concrete impact, but it remains within the framework of the Jordanian-European interest, and therefore it must continue to develop some of its aspects in an actual and serious manner so that the two parties can achieve fruitful cooperation within its framework.